Intussusception associated with rotavirus vaccination in a 2-month-old infant: A case report - Shu-Wei Hu; Min-Yung Kuo; Hueng-Chuen Fan (Tungs’ Medical Journal)
Abstract Intussusception is an intestinal disease usually occurring within 2 years of age. Most cases are idiopathic or caused by intestinal lymphadenopathy after viral infection. The rotavirus vaccine is a kind of oral live attenuated vaccine approved by the Department of Health in Taiwan since 2006. This vaccine reportedly increases the risk of intussusception, especially after the first dose. Herein, we report a case of intussusception after the first dose of oral rotavirus vaccination with surgical findings that could clarify the pathogenesis of rotavirus vaccine-induced intussusception.